Building Resilient Coastal Communities: The NHERI Experimental Facility for Surge, Wave, and Tsunami Hazards - Lomonaco, Pedro; Cox, Daniel; Higgins, Christopher; Maddux, Timothy; Bosma, Bret; Miller, Rebekah; Batti, James (Frontiers in Built Environment, 2020)
Through the Natural Hazards Engineering Research Infrastructure program (NHERI) established by the National Science Foundation in the United States, a suite of experimental facilities has been made available to the research community to advance the resilience of civil infrastructure and communities to coastal storm and earthquake hazards. An experimental facility called the NHERI Experimental Facility hosted at the O.H. Hinsdale Wave Research Laboratory at Oregon State University (HWRL EF) was created through this program that serves as a state-of-the-art engineering research, education, and outreach center related to tsunamis caused by earthquakes and coastal waves and surge caused by windstorms. HWRL EF includes two specialized large-scale resources for physical model testing of coastal systems: a large wave flume (LWF) and a directional wave basin (DWB). These facilities are available to the research community to address grand challenges relating to tsunami and coastal windstorm surge and wave hazards impacting the built and natural environments. This paper describes the capabilities of the HWRL EF and presents 10 example projects conducted under NHERI since 2016. The research projects highlight the broad scientific interest and potential application of physical model testing in multi-hazard mitigation and resilience in coastal communities.